“THE ROLE OF FOLK APPLIED ARTS IN ENHANCING CREATIVE AND AESTHETIC DEVELOPMENT OF SCHOOL-AGE CHILDREN” - Raxmonova Rayxon Zoir qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article investigates the significance of folk applied arts in fostering creativity, aesthetic sensibility, and cultural awareness in school-age children. Through hands-on activities such as designing traditional patterns, crafting ornaments, and experimenting with colors and shapes, children develop visual thinking, fine motor skills, and an appreciation for national heritage. The study highlights that integrating folk arts into educational practice promotes creativity, social interaction, and cultural literacy, providing an effective pedagogical approach for holistic child development.